Mycobiota and Natural Incidence of Aflatoxins, Ochratoxin A, and Citrinin in Indian Spices Confirmed by LC-MS/MS - Punam Jeswal; Dhiraj Kumar (International Journal of Microbiology)
Nine different Indian spices (red chilli, black pepper, turmeric, coriander, cumin, fennel, caraway, fenugreek, and dry ginger) commonly cultivated and highly used in India were analysed for natural occurrence of toxigenic mycoflora and aflatoxins (AFs), ochratoxin A (OTA), and citrinin (CTN) contamination. Aspergillus flavus and Aspergillus niger were the most dominant species isolated from all types of spices. Red chilli samples were highly contaminated with aflatoxins (85.4%) followed by dry ginger (77.7%). 56% Aspergillus flavus from red chilli and 45% Aspergillus ochraceus from black pepper were toxigenic and produced aflatoxins and ochratoxin A, respectively. Qualitative detection and quantitative detection of mycotoxins in spices were analyzed by ELISA and further confirmed by LC-MS/MS. Penicillium citrinum produced citrinin in red chilli, black pepper, coriander, cumin, fenugreek, and dry ginger samples. The highest amount of AFs was found in red chilli (219.6 ng/g), OTA was in black pepper (154.1 ng/g), and CTN was in dry ginger samples (85.1 ng/g). The results of this study suggest that the spices are susceptible substrate for growth of mycotoxigenic fungi and further mycotoxin production. This is the first report of natural occurrence of citrinin in black pepper and dry ginger from India.